Salvianolic Acid B Reduces Oxidative Stress to Promote Hair-Growth in Mice, Human Hair Follicles and Dermal Papilla Cells - Thianthanyakij T; Zhou Y; Wu M; Zhang Y; Lin JM; Huang Y; Sha Y; Wang J; Kong SP; Lin J; Liu Q; Wu W (Dove Medical Press, 2024)
Traidit Thianthanyakij,1,2,* Yinghui Zhou,1,* Mengyi Wu,3,* Yuting Zhang,4 Jui-Ming Lin,1 Yan Huang,4 Yuou Sha,1 Jiayi Wang,1 Sirapath Peter Kong,2 Jinran Lin,1 Qingmei Liu,1 Wenyu Wu1,5,6 1Department of Dermatology, Huashan Hospital, Fudan University, Shanghai Institute of Dermatology, Shanghai, 200040, People's Republic of China; 2Faculty of Medicine, Thammasat University (Rangsit Campus), Pathumthani, 12120, Thailand; 3Shanghai University of Traditional Chinese Medicine, Shanghai, 200032, People's Republic of China; 4State Key Laboratory of Genetic Engineering, Collaborative Innovation Center for Genetics and Development, School of Life Sciences, Fudan University, Shanghai, 200433, People's Republic of China; 5Department of Dermatology, Jing'an District Central Hospital, Shanghai, 200040, People's Republic of China; 6Academy for Engineering and Technology, Fudan University, Shanghai, 200433, People's Republic of China*These authors contributed equally to this workCorrespondence: Qingmei Liu; Wenyu Wu, Email liuqing.mei@163.com; wenyu_wu@fudan.edu.cnBackground: Existing research links oxidative stress and inflammation to hair loss. Salvianolic acid B (SAB) is known for its anti-oxidative, anti-inflammatory, and other beneficial pharmacological properties.Objective: To assess the efficacy of SAB in modulating hair growth.Methods: In vivo experiments were conducted using C57BL/6 mice to evaluate the effects of SAB on hair and skin parameters. The study involved ex vivo analysis of human hair follicles (HFs) for hair shaft length and hair growth cycle assessment. In vitro, human dermal papilla cells (hDPCs) were cultured with SAB, and their proliferation, protection against H2O2-induced oxidative damage, and gene/protein expression alterations were examined using various analytical techniques, including Real-Time Cell Analysis (RTCA), DCFH-DA Assay, RNA-seq, and KEGG pathway analysis.Results: SAB treatment in mice significantly improved hair growth and vascularization by day 21. In human HFs, SAB extended hair shaft length and delayed the transition to the catagen phase. SAB-treated hDPCs showed a notable decrease in the expression of oxidation-antioxidation-related genes and proteins, including reduced phosphorylation levels of ERK and p38.Conclusion: The study indicates that SAB promotes hDPC proliferation and offers protection against oxidative stress, highlighting its potential as a therapeutic agent for enhancing hair growth and treating hair loss.Keywords: salvianolic acid B, hair growth, hair cycle, hair follicle, dermal papilla cells